\(A=9x^2+2y^2+6xy-6x+11\)
=> \(A=9x^2+6x\left(y-1\right)+2y^2+11\)
=> \(A=\left(3x\right)^2+2.3x\left(y-1\right)+\left(y-1\right)^2-\left(y-1\right)^2+2y^2+11\)
=> \(A=\left(3x+y-1\right)^2-\left(y^2-2y+1\right)+2y^2+11\)
=> \(A=\left(3x+y-1\right)^2-y^2+2y-1+2y^2+11\)
=> \(A=\left(3x+y-1\right)^2+y^2+2y+1+9\)
=> \(A=\left(3x+y-1\right)^2+\left(y+1\right)^2+9\)
Có \(\left(3x+y-1\right)^2\ge0\)với mọi x; y
\(\left(y+1\right)^2\ge0\)với mọi y
=> \(\left(3x+y-1\right)^2+\left(y+1\right)^2+9\ge9\)với mọi x; y
=> \(A\ge9\)với mọi x; y
Dấu "=" xảy ra <=> 3x + y - 1 = 0 và y + 1 = 0
<=> 3x + y = 1 và y = -1
<=> x = -4 và y = -1
KL: Amin = 9 <=> x = -4 và y = -1